REVITALIZATION OF LOCAL WISDOM 'MAPALUS' IN PUBLIC SERVICE GOVERNANCE AND HANDLING SOCIAL PROBLEMS IN LANGOWAN TIMUR DISTRICT, MINAHASA REGENCY - Steven V. Tarore; Jeane Mantiri; Margareth I. R. Rantung (Journal of International Islamic Law, Human Right and Public Policy, 2026)
Public service governance at the sub-district and village levels in Indonesia often faces obstacles in the form of a rigid, top-down bureaucratic approach and minimal community participation. In Minahasa Regency, the local wisdom of Mapalus has historically proven effective in managing agrarian resources, but its use in public administration governance and handling modern social problems is still very limited. This study aims to formulate a Mapalus revitalization model in public service governance and handling social problems in East Langowan District. Using descriptive qualitative methods with secondary data analysis and literature review, this study found that Mapalus must transform from mere physical mutual cooperation to Collaborative Governance. The revitalization models offered include: (1) Administrative Mapalus to accelerate population services, (2) Social Mapalus to address stunting and poverty, and (3) Environmental Mapalus to mitigate natural disasters. The main challenges include the degradation of Mapalus values among the younger generation and the absence of a formal legal umbrella at the village level. This study recommends the integration of Mapalus into Village Regulations (Perdes) as a non-bureaucratic standard operating procedure (SOP) in public services.